Investigation of potential toxic components based on the identification of Genkwa Flos chemical constituents and their metabolites by high‐performance liquid chromatography coupled with a Q Exactive high‐resolution benchtop quadrupole Orbitrap mass spectrometer. Issue 16 (18th July 2018) - Wang, Zhipeng; Chu, Yanjie; Zhang, Yuanyuan; Chen, Yu; Zhang, Jingjing; Chen, Xiaohui
Abstract: Genkwa Flos, a famous traditional Chinese medicine has been reported to have significant hepatotoxicity. A high‐throughput and reliable method was established to explore potential toxic components by high‐performance liquid chromatography coupled with a Q Exactive high‐performance benchtop quadrupole‐Orbitrap mass spectrometer. A total of 68 compounds including 22 chemical components and 46 metabolites were tentatively identified based on the accurately measured mass value, retention time, and fragmentation pattern. Besides, the metabolic pathways of main components in Genkwa Flos were also illustrated. The results indicated that hydroxylation, demethylation, methylation, glucuronidation, sulfation, cysteine conjugation, and glutathione conjugation participated in the metabolic reactions of Genkwa Flos . Moreover, 12 Genkwa Flos chemical components and 26 metabolites were detected in cell lysate, which were considered as the bound components to HL‐7702 cells. In view of cell affinity theory, these compounds were preliminarily deduced to be potential toxic ingredients for the hepatotoxicity induced by Genkwa Flos . The results demonstrated that the developed method was a very feasible and efficient approach for the components identification even in the complex matrix. In conclusion, this study will provide a deep insight into the toxic substances of Genkwa Flos and lay a chemical basis for in‐depth toxic studies on Genkwa Flos hepatotoxicity.